2020
DOI: 10.1055/a-1236-4102
|View full text |Cite
|
Sign up to set email alerts
|

Knee Kinetics in Baseball Hitting and Return to Play after ACL Reconstruction

Abstract: The purpose of this study was to describe the knee kinetics of baseball hitting, develop a tool to predict knee kinetics from easily obtainable measures, and to compare knee kinetics to other exercises along the rehabilitation continuum to determine a timeline for when hitting may resume after ACL reconstruction. Nineteen high school baseball athletes (16.3±0.8 yrs, 180.6±5.7 cm, 78.4±10.8 kg) participated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Advancements in return to hitting protocols have been suggested by Giordano et al (35) following ACL reconstruction in 19 high school baseball athletes. Bilateral knee kinetic values were analyzed using knee extension torque, knee internal and external rotation torque, knee varus and valgus torque, and knee anterior force (35). Comparing kinetics of the baseball swing with those of rehabilitation exercises, it is suggested that tee hitting may be initiated at 13 wk postoperatively following ACL reconstruction on the front knee and 17 wk postoperatively on the back knee (35).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Advancements in return to hitting protocols have been suggested by Giordano et al (35) following ACL reconstruction in 19 high school baseball athletes. Bilateral knee kinetic values were analyzed using knee extension torque, knee internal and external rotation torque, knee varus and valgus torque, and knee anterior force (35). Comparing kinetics of the baseball swing with those of rehabilitation exercises, it is suggested that tee hitting may be initiated at 13 wk postoperatively following ACL reconstruction on the front knee and 17 wk postoperatively on the back knee (35).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Advancements in return to hitting protocols have been suggested by Giordano et al (35) following ACL reconstruction in 19 high school baseball athletes. Bilateral knee kinetic values were analyzed using knee extension torque, knee internal and external rotation torque, knee varus and valgus torque, and knee anterior force (35).…”
Section: Kneementioning
confidence: 99%
See 1 more Smart Citation